The importance of deradicalization in the process of social rehabilitation of a person - Mirakhmedova Dilafruz; Joraeva Gulshada (Peerian Journals Publishing, 2023)
Today, various international organizations and scientific research centers around the world emphasize that, in addition to paying special attention to social rehabilitation, it is necessary to prevent the factors that cause radicalization and strengthen deradicalization. During the study of individuals with destructive ideas in mind, it was found that they have an intolerant attitude towards people as a result of their unresolved views on existing issues and social problems. The increase in the number of people with such views has led to their becoming owners of destructive activities.
Keywords: rehabilitation; deradicalization; radicalism; globalization